2015
DOI: 10.1038/bjc.2015.351
|View full text |Cite
|
Sign up to set email alerts
|

Assessing vascular effects of adding bevacizumab to neoadjuvant chemotherapy in osteosarcoma using DCE-MRI

Abstract: Background:The purpose of this study was to assess the impact of bevacizumab alone and in combination with cytotoxic therapy on tumour vasculature in osteosarcoma (OS) using DCE-MRI.Methods:Six DCE-MRI and three 18F-FDG PET examinations were scheduled in 42 subjects with newly diagnosed OS to monitor the response to antiangiogenic therapy alone and in combination with cytotoxic therapy before definitive surgery (week 10). Serial DCE-MRI parameters (Ktrans, vp, and ve) were examined for correlation with FDG-PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Metabolic imaging modalities such as dynamic enhanced MRI and positron emission tomography may provide more accurate measurements of tumor response. 23 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic imaging modalities such as dynamic enhanced MRI and positron emission tomography may provide more accurate measurements of tumor response. 23 …”
Section: Discussionmentioning
confidence: 99%
“…The treatment schema is shown in Figure 1. Bevacizumab was administered 3 days before the first dose of chemotherapy at week 0 to characterize the single-dose single agent pharmacokinetics of the drug in children 22 and to assess the effect of bevacizumab alone on the tumor vasculature using dynamic contrast-enhanced MRI 23 , as previously reported. All subsequent doses of bevacizumab were given on day 1 of chemotherapy.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies indicate that anti-angiogenic therapies cause vascular normalization, [46,47]. Several studies have suggested that changes in K trans may be an early pharmacodynamic biomarker of clinical response to anti-angiogenics [48][49][50]. However, K trans denotes a context-dependent (including degree of tumor perfusion and MRI acquisition setup/equipment) complex combination of tissue blood flow and permeability weighted to varying extents.…”
Section: Discussionmentioning
confidence: 99%
“…OS99 involved carboplatin, ifosfamide, and doxorubicin . OS2008 added a monoclonal antibody, bevacizumab, to a combination of cisplatin, doxorubicin, and HDMTX …”
Section: Methodsmentioning
confidence: 99%